Interviewing children and young people for research - O'Reilly, Michelle; Dogra, Nisha (SAGE, 2017)
"This book provides a practical, pedagogical perspective on conducting qualitative interviews with children and young people.From designing and choosing the type of interview through to planning, structuring, conducting, and analysing them this book is a complete toolkit. Drawing upon real-world examples and researchers′ anecdotes, the authors combine both theoretical background and practical advice to introduce common issues and procedures and to help you undertake your own interviews in the field"--Provided by publisher.